Firm Litigation Risk and the Insurance Value of Corporate Social Performance - KOH, Ping-Sheng (Institutional Knowledge at Singapore Management University, 2014)
This paper advances the risk management perspective that superior social performance enhances firm value by serving as an ex ante valuable insurance mechanism. We posit that good social performance is more valuable as an insurance mechanism for firms with higher litigation risks. Moreover, value generation of corporate social performance (CSP) depends on whether a firm has gained pragmatic legitimacy (i.e., a firm's financial health) and moral legitimacy (i.e., whether or not a firm operates in a socially contested industry) among its stakeholders. We find that the value of CSP as insurance against litigation risk is practically significant, adding 2 to 4 percent to firm value. But CSP is less likely to create value if the firm is in financial distress or is operating in socially contested industries.